Consensus-based identification of factors related to false-positives in ultrasound scanning of synovitis and tenosynovitis. Issue 1 (2nd January 2016) - Ikeda, Kei; Narita, Akihiro; Ogasawara, Michihiro; Ohno, Shigeru; Kawahito, Yutaka; Kawakami, Atsushi; Ito, Hiromu; Matsushita, Isao; Suzuki, Takeshi; Misaki, Kenta; Ogura, Takehisa; Kamishima, Tamotsu; et al.
Abstract: Introduction : We aimed to identify causes of false-positives in ultrasound scanning of synovial/tenosynovial/bursal inflammation and provide corresponding imaging examples. Methods : We first performed systematic literature review to identify previously reported causes of false-positives. We next determined causes of false-positives and corresponding example images for educational material through Delphi exercises and discussion by 15 experts who were an instructor and/or a lecturer in the 2013 advanced course for musculoskeletal ultrasound organized by Japan College of Rheumatology Committee for the Standardization of Musculoskeletal Ultrasonography. Results : Systematic literature review identified 11 articles relevant to sonographic false-positives of synovial/tenosynovial inflammation. Based on these studies, 21 candidate causes of false-positives were identified in the consensus meeting. Of these items, 11 achieved a predefined consensus (≥ 80%) in Delphi exercise and were classified as follows: (I) Gray-scale assessment [(A) non-specific synovial findings and (B) normal anatomical structures which can mimic synovial lesions due to either their low echogenicity or anisotropy]; (II) Doppler assessment [(A) Intra-articular normal vessels and (B) reverberation)]. Twenty-four corresponding examples with 49 still and 23 video images also achieved consensus. Conclusions : Our study provides a set of representative images that can help sonographers to understand false-positives in ultrasound scanning of synovitis and tenosynovitis.